BANKRUPTCY PREVENTION ISSUES IN THE CONTEXT OF FINANCIAL STABILITY - Mnatsakanyan, Grigor; Sargsyan, Varsenik; Tepoyan, Vahagn (Bulletin of Yerevan University G: Economics, 2019)
Ensuring the financial sustainability of the country’s economy greatly affects the solvency of companies and later, as well, on bankruptcy prevention. Comparative analysis of the financial sustainability indicators of the EAEU countries is presented in the work. Studying the extent to which organizations’ liabilities and overdue debts are measured in terms of the countries surveyed, an assessment of the financial stability and bankruptcy indicators of EAEU has been implemented by means of an integrated assessment of the financial position. Having examined the commitments and overdue debts of the organizations on the basis of the countries under consideration, through the integrated assessment method of the financial condition has been carried out an assessment of the financial stability and bankruptcy risk indicators of the EAEU commercial organizations